2020
DOI: 10.6004/jnccn.2019.7342
|View full text |Cite
|
Sign up to set email alerts
|

High-Cost Patients and Preventable Spending: A Population-Based Study

Abstract: Background: Although high-cost (HC) patients make up a small proportion of patients, they account for most health system costs. However, little is known about HC patients with cancer or whether some of their care could potentially be prevented. This analysis sought to characterize HC patients with cancer and quantify the costs of preventable acute care (emergency department visits and inpatient hospitalizations). Methods: This analysis examined a population-based sample of all HC patients in Ontario in 2013. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 41 publications
(50 reference statements)
0
10
0
Order By: Relevance
“…Examining the difference between blood cancers and solid tumors specifically, existing studies have demonstrated that the clinical course, treatment options, and overall morbidity and mortality among the two types of cancers are fundamentally different [ 26 , 27 , 28 , 29 , 30 , 31 ]. These differences have significant implications for the financial toxicity experienced by patients and survivors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Examining the difference between blood cancers and solid tumors specifically, existing studies have demonstrated that the clinical course, treatment options, and overall morbidity and mortality among the two types of cancers are fundamentally different [ 26 , 27 , 28 , 29 , 30 , 31 ]. These differences have significant implications for the financial toxicity experienced by patients and survivors.…”
Section: Discussionmentioning
confidence: 99%
“…We found that respondents with blood cancers reported increased medical utilization and distress over the medical costs of healthcare and paying medical bills compared to those with solid tumors. The high costs associated with providing care to patients with blood cancers are well documented [ 23 , 26 , 28 , 39 ]. Our study corroborates these findings, as respondents with blood cancers reported a higher level of medical care utilization, especially in the domains of length and frequency of hospitalizations, as well as the number of outpatient visits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Higher costs have also been associated with clustering in overall health care expenditures. [7][8][9][10][11][12] It is unclear to what extent the overall growth in drug expenditure is driven by this same occurrence.Canada is currently the only high-income country with a universal health insurance system that does not provide universal coverage of prescription drugs, 13 in contrast to Australia, which has a publicly funded Pharmaceutical Benefits Scheme (PBS). Recently, there has been increasing pressure to establish a national drug coverage program in Canada, similar to Australia's PBS.…”
mentioning
confidence: 99%
“…6 Higher costs have also been associated with clustering in overall health care expenditures. [7][8][9][10][11][12] It is unclear to what extent the overall growth in drug expenditure is driven by this same occurrence.…”
mentioning
confidence: 99%